Desenvolvimento, caracterização e desempenho de novos eletrodos para dispositivos eletromecânicos baseados em nanocompósitos elastoméricos condutores tratados por plasma - Barbosa, Rafael (2022)
Ionomeric polymer-metal composites (IPMC) are devices generally composed of metallic electrodes and an ionomeric polymer membrane in a “sandwich-like” format, whose main property is the electromechanical actuation or sensing due to ions movement. Metal electrodes are used for their high electrical conductivity and malleability. However, the high cost of the material, long manufacturing time, and fatigue failure limit its application both economically and in durability. In this sense, the replacement of metallic electrodes with conductive elastomer nanocomposites was evaluated to reduce the costs and complexity of device manufacturing and increase its operating life. Two processing routes were used to prepare the synthetic and natural polyisoprene elastomers, one with subsequent homogenization by a two-roll mill and the other by casting. The dispersion of the conductive fillers (carbon nanotubes and carbon black) was carried out in rubber latex assisted by surfactants and ultrasound. The prepared nanocomposites showed high electrical conductivity as well as strain and solvent sensing capacities. To improve the adhesion between the elastomers and the membrane (Nafion®), the plasma treatment with atmospheric air was evaluated as a surface modifier. This treatment improved the hydrophilicity and the adhesion work of the rubbers with the formation of oxygenated groups and an increase in nano-roughness. However, in Nafion an adverse effect of side chains breakage occurred, impairing its ionic transport capacity. In this way, ionomeric polymer-polymer composites (IPPC) were prepared using untreated Nafion and plasma-modified elastomers, this type of electrode being unprecedented in the literature. These devices presented displacement and trajectory sensing capacity at levels close to the conventional IPMC in all frequency ranges and applied accelerations, highlighting that at low frequencies the IPPC obtained better results than the control.